Shape morphing metamaterials via pressure actuated shape morphing cells - Ankit Saxena; Christopher Rahn; Guha Manogharan (Virtual and Physical Prototyping)
The ability to fully achieve shape-morphing functionality and tunable mechanical properties is constantly desired to push the current boundaries of robotics, smart structures, aerospace, and defense applications. While shape change has been extensively explored in soft materials, they are often unsuitable for load-bearing structural applications. In this work, a new class of monolithic metamaterials with Pressure-actuated shape-morphing Cells (labelled ‘PASCells’) is demonstrated for shape-morphing functionality in rigid structures. The novelty in the presented PASCells lies in achieving high elastic strains in load-bearing structural members by selectively pressurising fluidic cells that can now be additively manufactured. This new metamaterial functionality can be realised at multiple length scales for a wide range of loading conditions with on-demand shape-morphing and tuning of mechanical responses. The analytical methods and experimental characterisation presented in this paper are foundational to achieving shape-morphing in high-performance structural applications such as airfoils in aerospace and wind turbines.